Immunometabolic reprogramming in diabetic osteomyelitis: from mechanisms to therapeutics - Zhang, Hui; Fu, Zi-Shan; Zhou, Ying; Wang, Song-Nan; Ye, Si-Ying; Wang, An-Na; Liu, Jun-Tong (Frontiers in Cellular and Infection Microbiology, 2025)
Diabetes mellitus (DM) is a globally prevalent metabolic disorder characterized by impaired immune function due to poor glycaemia control, significantly increasing the risk of osteomyelitis. The occurrence of bone infection not only compromises patients’ quality of life but also poses substantial challenges in clinical management. Recent studies have identified immunometabolic reprogramming as a pivotal player in the pathogenesis and progression of diabetic osteomyelitis. This reprogramming not only disrupts immune cell functionality but also modulates the local microenvironment, thereby impairing bone repair processes. Although preliminary research has explored the underlying mechanisms, a comprehensive understanding of the precise role of immunometabolic reprogramming and its potential therapeutic targeting in diabetic osteomyelitis remains elusive. This review synthesizes current advances in immunometabolic reprogramming within diabetic osteomyelitis, elucidates its biological mechanisms, and proposes novel intervention strategies to inform clinical practice and inspire future therapeutic development.